Perfuração de intestino delgado por doença diverticular jejunal - Leal,Vilmar Moura (2010)
Small Intestine's diverticulosis is an uncommon pathology of intestine. It's more evident at jejune and can be complicated by intestinal perforation, obstruction or diverticulitis, increasing the mortality. We describe a forty years old female patient that arrived at emergency service complained of diffuse abdominal pain. There aren't signals of peritonitis and the radiological evaluation showed small intestine's distension. Surgical intervention was performed revealing multiples diverticulums at jejune and intestinal perforation. The aim of this article is present a case of Small Intestine's diverticulosis and its complications that had precise intervention resulting in a favorable resolution.